تقويم أداء مدرسي مادة الأحياء في ضوء مهارات القرن الحادي والعشرين - رحيم، أحمد عبدالأمير (كلية العلوم الإنسانية والاجتماعية, 2020)
This research aimed to Evaluating the performance of the teachers of biology in light of the 21st Century skills , and identification the availability of this skills in the performance of teachers of biology (32) teachers in Al-Qadisiyah 2018-2019 . The researcher has used an observation as a tool for valuating and judging the performance and scientific skills of biology teachers. The researcher has formulated a list of learning dimensions skills including (10) skills Learning and innovation, Information, Media and Technology, and Life & career skills. The finding has proved that three skills highly statistically significant of teacher performance, five are moderately statistically significant to teacher performance, and two are low statistically significant to teacher performance.
هدف البحث الحالي إلى تقويم أداء مدرسي مادة علم الأحياء في ضوء مهارات القرن الحادي والعشرين، والتعرف على مدى توافر هذه المهارات في أداء مدرسي مادة علم الأحياء عينة البحث المكونة من (32) مدرس في محافظة القادسية للعام الدراسي 2018- 2019، وقد استخدم الباحث بطاقة ملاحظة أداة للبحث لتقويم أداء مدرسي مادة علم الأحياء والحكم على مستوى أداءهم ومهاراتهم العلمية، وقد توصل الباحث إلى قائمة بمهارات القرن الحادي والعشرين تضمنت (10) مهارات فرعية تندرج تحت ثلاث مهارات رئيسية هي: مهارات التعلم والإبداع، مهارات التمكن المعلوماتي والإعلام، والتكنولوجيا، ومهارات الحياة والعمل. وقد تحققت ثلاث مهارات بدرجة كبيرة في أداء المدرسين، وخمسة بدرجة متوسطة، واثنتان بدرجة قليلة من مهارات القرن الحادي والعشرين.
Keywords: الإدارة التعليمية -- معلمو مادة الأحياء -- التأهيل المهني -- تقييم الأداء -- القرن الحادي والعشرين